2020
DOI: 10.21203/rs.3.rs-15704/v4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pre-hospital delay in patients with myocardial infarction: an observational study in a tertiary care hospital of northern Bangladesh

Abstract: Abstract Background: Delayed hospital presentation is a hindrance to the optimum clinical outcome of modern therapies of Myocardial infarction (MI). This study aimed to investigate the significant factors associated with prolonged pre-hospital delay and the impact of this delay on in-hospital mortality among patients with MI in Northern Bangladesh.Methods: This cross sectional study was conducted in December 2019 in cardiolo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Late arrival from onset of symptoms to hospital is the major cause of increasing morbidity and mortality rate in acute myocardial patients [13], and ST elevation myocardial infarction is one of the leading causes of mortality and morbidity worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…Late arrival from onset of symptoms to hospital is the major cause of increasing morbidity and mortality rate in acute myocardial patients [13], and ST elevation myocardial infarction is one of the leading causes of mortality and morbidity worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was consistent with previous literature. One study in India noted that longer distance, rural residence, and issues with transportation were found to be predictors for late presentation [ 14 ]. This same study also noted that this variable may not be generalizable to other populations as all areas and locations differ in health-seeking behavior and sociodemographic factors [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…One study in India noted that longer distance, rural residence, and issues with transportation were found to be predictors for late presentation [ 14 ]. This same study also noted that this variable may not be generalizable to other populations as all areas and locations differ in health-seeking behavior and sociodemographic factors [ 14 ]. Another study found that although some individuals lived farther from the hospital, they only used ambulance services about 5% of the time, which may have indicated the lack of understanding of the importance of early EMS contact and the sense of urgency that is warranted with acute treatment [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 7 ] Therefore, reducing the delay in starting standard treatments such as reperfusion therapy is a critical strategy to increase the success rate of treatment in AMI. [ 8 ]…”
Section: Introductionmentioning
confidence: 99%